Braquiterapia epiescleral con iridio 192 en melanoma uveal: experiencia en el Instituto Nacional de Enfermedades Neoplásicas en el período 1996 - 2010 - Cordero Garcia Zapatero, Raul Salvador (2017)
Objective: Evaluate the efficacy of Episcleral Brachytherapy with Iridium 192 as an alternative to Iodine 125 for the treatment of Uveal Melanoma. Materials and Methods: We treated 23 patients with diagnosis of Uveal Melanoma with Iridium 192 adhered to a gold plaque, during a 14 year period. Results: The rate of ocular complications was 69,6% and the rate of ocular conservation was 69,6%. The survival rate for 5 years was 95,7%. Conclusions: Episcleral Brachytherapy with Iridium 192, in our experience, is effective in treating Uveal Melanoma, obtaining similar results as other institutions.